Validation of the Korean Version of the Anticipatory and Consummatory Interpersonal Pleasure Scale in Non-help-seeking Individuals - Kim, Eunhye; Gooding, Diane C.; Lee, Tae Young (Frontiers in Psychology, 2022)
The Anticipatory and Consummatory Interpersonal Pleasure Scale (ACIPS) is a psychometric instrument that has been used to indirectly measure social anhedonia in many cross-cultural contexts, such as in Western (US), European (French, Spanish), Eastern (Chinese), and Israeli samples. However, little is known about the psychometric properties of the ACIPS in Korean samples. The primary goal of this study was to validate the Korean version of the ACIPS among non-help-seeking individuals. The sample consisted of 307 adult individuals who had no current or prior psychiatric history. Participants were administered the ACIPS, along with the Behavioral Inhibition and Behavioral Activation Scales (BIS/BAS) and Beck Depression Inventory (BDI). We examined the association of the total ACIPS scores with the other measures. The ACIPS showed good internal consistency. We also explored the factor structure of the Korean translation of the ACIPS using principal component analysis with Promax rotation and Kaiser normalization. Factor analysis yielded a three-factor structure that accounted for 58.8% of the variance. The three-factor model included the following subdomains: interactions involving close relationships, casual interactions, and interactions involving family members. Total BAS and BIS scores were significantly associated with total ACIPS scores, while BDI scores were inversely associated with total ACIPS scores. The current research indicates that the Korean version of the ACIPS is a useful and valid scale. Future directions include using the Korean translation of the ACIPS to elucidate the varying degrees of hedonic capacity in psychiatric patients.